FOSTERING COLLABORATIVE ENGAGEMENT: STRATEGIES FOR STAKEHOLDER COOPERATION IN EARLY CHILDHOOD EDUCATION IN ZAMBIA - Joyce Mbewe; Blandina Manditereza (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Investigated strategies for stakeholder cooperation in Early Childhood Education (ECE) in Zambia. Emphasized collaboration between government, educators, families, and community organizations. Applied an interpretivist-phenomenological design with qualitative methods (interviews, observations, document review). Involved 10 purposively selected participants. Identified key barriers and enablers of stakeholder engagement. Recommended improved communication, stakeholder training, and formal collaboration policies.